PENERAPAN PENDEKATAN KONSTRUKTIVISME DALAM PEMBELAJARAN MATEMATIKA DI SD/MI - Karmawati, Karmawati (Fakultas tarbiyah dan Ilmu Keguruan Institut Agama Islam Negeri Palu, 2017)
Mathematics is one of the areas of study that must be studied at elementary level (SD /MI). The intellectual development of SD/MI students is still at the concrete operation stage, so that a teacher in presenting mathematics material needs to master the material of mathematics study which he/she teaches as well as the mastery of mathematics learning strategy and approach, in this case the approach of learning in elementary school. Learning is more than just remembering. For students, to understand and be able to apply science, they must work to solve problems, find something for themselves, and always grapple with ideas. Students should build their knowledge in their own minds, teachers can assist in this process, by means of teaching that make information very meaningful and highly relevant to students, by allowing them to discover and apply their own ideas and by encouraging students to be aware of and consciously using their own strategies for learning. This approach is called constructivist approach.